Contribution of phage‐derived genomic islands to the virulence of facultative bacterial pathogens. (4th October 2012) - Busby, Ben; Kristensen, David M.; Koonin, Eugene V.
Summary Facultative pathogens have extremely dynamic pan‐genomes, to a large extent derived from bacteriophages and other mobile elements. We developed a simple approach to identify phage‐derived genomic islands and apply it to show that pathogens from diverse bacterial genera are significantly enriched in clustered phage‐derived genes compared with related benign strains. These findings show that genome expansion by integration of prophages containing virulence factors is a major route of evolution of facultative bacterial pathogens.